Boron-Containing Compounds as Preventive and Chemotherapeutic Agents for Cancer - I. Scorei, Romulus; Popa, Radu (Anti-Cancer Agents in Medicinal Chemistry, 2010)
In the last few years boron (B) compounds became increasingly frequent in the chemotherapy of some forms of cancer with high malignancy and of inoperable cancers. As more B-based therapy chemicals are developed it is necessary to review the correlation between B and the incidence of different forms of cancer, the biochemical and molecular mechanisms influenced by B and to explore the relevance of B in the chemoprevention of cancer. This minireview analyzes dietary and therapeuptic principles based on the chemistry of B compounds. We summarize studies correlating B-rich diets or B-rich environments with regional risks of specific forms of cancers, and studies about the utilization of natural and synthetic B-containing compounds as anticancer agents. We review mechanisms where B-containing compounds interfere with the physiology and reproduction of cancer cells. Types of cancers most frequently impacted by B-containing compounds include prostate, breast, cervical and lung cancer. Mechanisms involving B activity on cancer cells are based on the inhibition of a variety of enzymatic activities, including serine proteases, NAD-dehydrogenases, mRNA splicing and cell division, but also receptor binding mimicry, and the induction of apoptosis. Boron-enriched diets resulted in significant decrease in the risk for prostate and cervical cancer, and decrease in lung cancer in smoking women. Boron-based compounds show promising effects for the chemotheraphy of specific forms of cancer, but due to specific benefits should also be included in cancer chemopreventive strategies.
Keywords: Boron